The Role of the Good Corporate Gorvernance Mechanism in Mitigating Profit Management Practices - Khoirunnisa, Sabrina; Wijoyo, Amin (Devotion : Journal of Research and Community Service, 2025)
This study aims to examine the influence of audit committees, institutional ownership, and independent commissioners as part of good corporate governance on earnings management practices in energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research sample consists of 57 energy companies selected through purposive sampling. Earnings management is measured using the Modified Jones Model, while the independent variables are assessed using indices and ratios. The data were analyzed using panel data multiple regression with EViews 12 software. The results indicate that the audit committee has a significant negative effect on earnings management, institutional ownership has a significant positive effect, while the independent commissioners have a negative but statistically insignificant effect. These findings underscore the need to strengthen corporate governance substantively, particularly by enhancing the active role of institutional investors and improving the independence and competence of board members.